(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Urinary tract infections are currently among the most common infectious diseases observed in pregnant women. They negatively affect not only the mother’s health but also the development of the foetus. The World Health Organization has provided definitions regarding urinary tract infections and developed treatment guidelines. A study was conducted at the Termiz branch of the Republican Specialised Scientific-Practical Medical Centre for Maternal and Child Health, in the Gynaecology and Pregnant Patients Departments, involving 90 pregnant and postpartum women diagnosed with urinary tract infections. This article highlights the causes, types, clinical manifestations, principles of early diagnosis and treatment, as well as preventive measures of urinary tract infections during pregnancy.